Los recursos didácticos en el proceso de enseñanza-aprendizaje para el manejo de programas utilitarios en la materia de computación en estudiantes de primer año de bachillerato paralelos "A", "B", "C" jornada matutina de la unidad educativa "Juan Montalvo" de la ciudad de Machala provincia de El Oro 2012 - Aguayo Mora, Jessenia Marlene (2014)
The development of this thesis entitled, " THE TEACHING RESOURCES IN THE PROCESS OF LEARNING PROGRAMS FOR THE MANAGEMENT OF UTILITIES IN THE MATTER OF COMPUTERS IN FRESHMEN OF PARALLEL BACHELOR "A" " B " "C " DAY MORNING OF EDUCATION " JUAN MONTALVO " UNIT OF THE CITY OF GOLD MACHALA province the El Oro . 2012 " , is a diagnostic research work - aimed at determining purposeful teaching resources used in learning utility, for which a methodological process based on inductive, deductive, descriptive statistical methods are developed , the hypothetical and techniques of observation, interviews, surveys and signing. The investigative process allowed to conclude that the teaching support resources used by teachers in the PEA computer classes to teach utilities are traditional type, because the institution does not have a computer lab quality, which prevents students to apply theoretical knowledge learned in the classroom.